Legal Review of the Authority of Financial Services Authorities in Crime Practicesinsider Trading in Capital Markets in the Development of Information Technology - Asnawi, M. Iqbal; Fitriani, Rini; Isnaini, Nazar; Mutiarani, Rosy; Herlambang, M. Hafiz; Martin, Christopher (Mahadi: Indonesia Journal of Law, 2024)
The practice of insider trading constitutes a violation or crime within the Indonesian capital market, necessitating a legal role to safeguard investors against frequent violations in the market. This research delves into the legal role in addressing insider trading practices within the Indonesian capital market. The objectives include identifying the characteristics of insider trading in the Indonesian capital market and discerning the legal responsibilities associated with such practices. The research addresses the following issues: First, the characteristics of insider trading in the Indonesian capital market; and second, legal responsibilities concerning insider trading practices in the Indonesian capital market. This study employs a deductive-analytic juridical-normative approach. The analysis reveals that, firstly, the provisions on insider trading in capital markets law have not effectively ensured maximum protection for investors in Indonesia. Secondly, there are hindrances to offering comprehensive legal protection to investors in light of insider trading practices within the capital market.